Single crystal growth of the ErPd2Si2 intermetallic compound - Cao, Chongde; Klingeler, Rüdiger; Leps, Norman; Behr, Günter; Löser, Wolfgang (Journal of crystal growth, 2014)
Bulk single crystals of ErPd2Si2 with ThCr2Si2-type body-centered tetragonal structure have been successfully grown under a purified Ar atmosphere at a velocity of 10mm/h using a floating zone method with optical radiation heating. The preferred crystal growth direction is close to the [110] orientation with an inclination angle of 15° against the rod axis. The as-grown crystals are Pd-depleted with respect to their nominal stoichiometry ErPd2Si2. The crystals contain small Er-oxide particles. The single-crystalline specimen shows antiferromagnetic ordering indicated by a λ-type singularity of the specific heat capacity cp(T) at TN=3.4K. A broad anomaly around 15-20K in the magnetic contribution to cp(T) indicates two-level Schottky-type behavior similar to that of PrPd2Si2.